Heat stress and strain in exercise and sport - Brotherhood, J. R. (Journal of Science and Medicine in Sport, 2008)
Heat stress arising from the thermal environment is of concern to sports medicine and to sports administration because of the perceived risk of heat casualties, in particular heat stroke. Many sports organizations recommend environmental indices such as the WBGT for assessing risk and setting environmental limits for training and competition. But the limits are not justified by evidence. This article describes the nature of heat stress in sport and how it may be assessed objectively. Heat stress and the principal human responses to exercise heat stress are reviewed briefly. Metabolic heat production and the thermal environment provoke separate and largely independent physiological strains. Metabolic heat production drives body core temperature, and the thermal environment drives skin temperature; the combined stresses are integrated to drive sweat rate. Control of core temperature depends on adequate sweat production and the capacity of the environment to evaporate the sweat. The nature of exercise heat stress is demonstrated by rational analysis of the physical heat exchanges between the body and the environment. The principles of this analysis are applied to critical review of current practice in the assessment of heat stress in sport. The article concludes with discussion of research to establish methods for objective sport-specific assessment of heat stress.